Vinca alkaloids and analogues as anti-cancer agents: Looking back, peering ahead. Issue 17 (15th September 2018) - Martino, Emanuela; Casamassima, Giuseppe; Castiglione, Sonia; Cellupica, Edoardo; Pantalone, Serena; Papagni, Francesca; Rui, Marta; Siciliano, Angela Marika; Collina, Simona
Graphical abstract: Highlights: Natural sources provide the 60% of currently-used anticancer agents. Microtubule-targeting agents have a high therapeutic potential but side effects. Vinca alkaloids are the earliest microtubule-targeting agents approved for clinical use. Medicinal chemistry approaches led to the discovery of new effective derivatives. Innovative Vinca alkaloids-based therapies are under investigation. Abstract: Cancer still represents a "nightmare" worldwide, causing annually millions of victims. Several antiproliferative molecules are currently used as drugs market and offer a pharmaceutical opportunity for attenuating and treating tumor manifestations. In this context, natural sources have a relevant role, since they provide the 60% of currently-used anticancer agents. Among the numerous natural products, acting via different mechanisms of action, microtubule-targeting agents (MTAs) have a high therapeutic potential, since they disrupt the abnormal cancer cell growth, interfering with the continuous mitotic division. Vinca alkaloids (VAs) are the earliest developed MTAs and approved for clinical use (Vincristine, Vinblastine, Vinorelbine, Vindesine, and Vinflunine) as agents in the treatment of hematological and lymphatic neoplasms. Here, we review the state-of-art of VAs, discussing their mechanism of action and pharmacokinetic properties and highlighting their therapeutic relevance and toxicological profile. Additionally, we briefly disclosed the technological approaches faced so far to ameliorate the pharmacological properties, as well as to avoid the drug resistance. Lastly, we introduced the recent advances in the discovery of new derivatives.